The impact of cytological diagnosis of undetermined atypias in public health system - Pereira, Sônia M.M.; Yamamoto, Luzia S.U.; Loreto, Celso Di; Silva, Luciana A.; Makabe, Sérgio; Marques, José A.; Maeda, Marina Y.S.; Santoro, Carmen L.; Utagawa, Maria Lúcia; Longatto Filho, Adhemar (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: in order to optimize the morphological analysis of the cases with uncertain diagnosis, we critically analyzed the cases with Atypia ofSquamous Cells of Undertemined Significance (ASCUS) in cytological samples of uterine cervix collected in conventional smears (CS) and liquid-based preparations (LBC) an to correlate the findings with Hybrid Capture II (HC2) assay and biopsy. Objective:to evaluate the meanig of undeter-mined cytological atypia in relation to HPV infection detected by hybrid capture II test.Methods:97 cases taken from women examined at PerolaByignton Hospital, São Paulo, Brazil, during the year of 2002. The conventional smears were taken previously than LBC. The residual sample wasplaced in liquid-medium and LBC preparation with DNA-Citoliq system was performed. If at least one of the paired samples were classified asASCUS, the pair was submitted to a guided revision in order to evaluate the type of alteration taken in account to categorized ASCUS. Results: from97 cases studied, 14 were categorized as ASCUS by the two methods simultaneously. The others had different classification under or hyper estimat-ed. Six cases diagnosed as squamous intraepithelial lesion (SIL) by CS were ASCUS by LBC; in contrary, 19 ASCUS by CS were SIL by LBC.Eleven ASCUS by CS were diagnosed as negative by LBC, but CS categorized 47 LBC ASCUS as negative. From the morphological parameters nu-clear enlargement and coarse chromatin were regarded as ASCUS. From 68 ASCUS by LBC, 36 were HC2 positive for high risk HPV (hr-HPV): tenof them with biopsy proven lesion. From 42 CS ASCUS, 23 were hr-HPV positive, but only 7 with histological lesion. Conclusion:our results rein-forced the hypothesis that ASCUS is poorly reproducible by morphological examination by CS or LBC preparations. To add HC2 as adjunct methodto ASCUS cytology can improve the routine diagnosed of the uncertain atypies.